Advancing sustainable manufacturing: a case study on plastic recycling - Javier Maldonado-Romo; Rafiq Ahmad; Pedro Ponce; Juana Isabel Mendez; Omar Mata; Mario Rojas; Luis Montesinos; Arturo Molina (Production and Manufacturing Research: An Open Access Journal)
This paper reviews sustainable manufacturing practices by integrating environmental, economic, and social dimensions of sustainability, emphasizing that environmental aspects are most frequently addressed (53.8%), followed by economic (34.6%) and social (11.5%) dimensions. Key findings identify crucial practices for sustainability across materials, products, processes, and supply chains, particularly sustainable materials derived from natural, renewable, or waste sources. An analysis of 17,694 articles highlights trends and gaps, linking practices to life cycle stages and Sustainable Development Goals (SDGs), notably SDG#9 and SDG#12. A proposed framework emphasizes continuous environmental performance improvement through quantitative analysis using the Life Cycle Engineering (LCE) framework, enhancing competitiveness and reducing environmental impact. The LCE framework case study demonstrates how waste materials, like plastic bottles, can be repurposed as raw materials, illustrating its value, especially for small and medium-sized enterprises, and highlighting the importance of integrating sustainability from the ideation stage.